Determinants for Perinatal Mortality in South China: A Prospective Cohort Study - Yiping Liu; Qiongxuan Li; Tingting Wang; Tingting Wang; Senmao Zhang; Letao Chen; Yihuan Li; Jingyi Diao; Jinqi Li; Xinli Song; Mengting Sun; Jianhui Wei; et al. (Frontiers Media S.A., 2022)
ObjectiveTo estimate the association of selected maternal and fetal characteristics with the risk of perinatal mortality in South China.MethodsA prospective cohort study was conducted from March 2013 to December 2019. The exposures of interest were maternal sociodemographic characteristics, lifestyle and habits during early pregnancy, and complications of pregnancy. Their effects on the development of perinatal death were analyzed in our study.ResultsA total of 44,048 eligible pregnant women were included in the analysis. Of these, 596 fetuses were perinatal deaths (perinatal mortality was 13.5 per 1,000 births). After adjustment, maternal obesity, being employed, history of gestational hypertension, taking antidepressants during early pregnancy, history of gestational diabetes mellitus, gestational diabetes mellitus, infertility drug treatment and assisted reproductive techniques, history of neonatal death, preterm birth, and congenital malformations all significantly increased the risk of perinatal death. Ethnic minority, income > 5,000, multiparous women, and cesarean section associated with reduced risk of perinatal death.ConclusionSome factors of maternal sociodemographic characteristics, abnormal pregnancy history, lifestyle and habits during early pregnancy, and complications of pregnancy were associated with the risk of perinatal death.